1967
DOI: 10.1111/j.1365-2672.1967.tb00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipolytic Micrococci in Pork Fat

Abstract: Summary. The lipolytic activity of Micrococcaceae on pork fat was investigated by their growth in a fat containing medium. Thirty‐three free fatty acids were detected of which 6 had a carbon chain with < 8 atoms, and were not present in the original fat. In addition to the free fatty acids the formation of 15 carbonyl compounds was detected, most of which were identified. The result of these investigations, and their influence on the microflora of dry sausages has been analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Most bacterial lipases have their activity at a neutral pH (Papon and Talon, 1989). Among lipolytic bacteria found in meat only certain Micrococcaceae and P. fragi have been shown to be lipolytic against natural pork fat (Cantoni et al, 1967;Debevere et al, 1976). Lipolytic activity of lactobacilli strains and Brochothrix thermosphacta is cell-related.…”
Section: Lipasementioning
confidence: 97%
“…Most bacterial lipases have their activity at a neutral pH (Papon and Talon, 1989). Among lipolytic bacteria found in meat only certain Micrococcaceae and P. fragi have been shown to be lipolytic against natural pork fat (Cantoni et al, 1967;Debevere et al, 1976). Lipolytic activity of lactobacilli strains and Brochothrix thermosphacta is cell-related.…”
Section: Lipasementioning
confidence: 97%
“…In Europe they have a long history, originating from Mediterranean countries during Roman times (28). Extensive studies have been performed on the characterization of traditional sausages produced in Greece, Italy, and Spain (4,9,10,15,16,21,31,38,(41)(42)(43)(44). A wide variety of microorganisms have been isolated from sausage fermentations by traditional methods.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion for lipases of bacteria curing these fatty acids through the production and involved in development of flavor. Cantoni, et al, in another study observed that, during dry italian sausages ripening, Lactobacilleae and Micrococcaceae play a signifcants role in the development of flavor [60]. Certain species of Micrococcus have been especially to nonvolatile and numerous volatile fatty acids and the fat of pork were detected in ripened-sausages.…”
Section: Meat Productionmentioning
confidence: 99%